The Effect of Academic Supervision, Work Happiness and Integrity on Teacher Performance Mediated Trust of State High School Principals in West Tanjung Jabung Regency - Elwardiansyah, M Haris; Masbirorotni; Aprollitzavivayarti (Jurnal Pendidikan Edutama, 2026)
This study aims to analyze the influence of academic supervision, job satisfaction, and integrity on teacher performance, with trust in the principal as a mediating variable in public high schools in West Tanjung Jabung Regency. Using a quantitative approach with Structural Equation Modeling (SEM-PLS) analysis techniques through SmartPLS 4, this study involved 139 teachers as a sample. The results showed that integrity significantly influenced teacher performance, while job satisfaction and academic supervision significantly influenced trust in the principal. However, integrity did not influence trust, and trust in the principal did not significantly influence teacher performance. Furthermore, academic supervision and job satisfaction had no direct effect on performance, and all mediation pathways through trust in the principal were declared insignificant. These findings emphasize the importance of strengthening integrity and a more comprehensive professional development strategy to improve teacher performance.